Flood Regulation Ecosystem Services Performance Based On Slope And Land Cover To Support Soil And Water Conservation In Ternate City - adriani; Muh. Faedly H. Tidore; Nurfadhilah Arif; Sabaruddin B (Universitas Sulawesi Barat, 2026)
Ternate City is a multi-island municipality characterized by diverse topographic and ecological conditions, exposing it to significant risks of surface runoff, inundation, and flash floods, consequences of its steep volcanic terrain and rapid land cover change. Flood regulation ecosystem services play a critical role in soil and water conservation and sustainable spatial planning. This study assessed the performance of flood regulation ecosystem services based on slope gradient (landform) and land cover across Ternate City using secondary spatial data from the 2022 Environmental Carrying and Assimilation Capacity Document (D3TLH), computed via the Simple Additive Weighting (SAW) method with a 1